An Endoplasmic Reticulum-Targeted Ratiometric Fluorescent Molecule Reveals Zn2+ Micro-Dynamics During Drug-Induced Organelle Ionic Disorder - Fang, Hongbao; Li, Yaheng; Yao, Shankun; Geng, Shanshan; Chen, Yuncong; Guo, Zijian; He, Weijiang (Frontiers in Pharmacology, 2022)
The endoplasmic reticulum (ER) is the main storage site of Zn2+, and Zn2+ plays an important role in regulating ER homeostasis. Therefore, we designed and synthesized a ratiometric fluorescent Zn2+ probe ER-Zn targeting ER stress. The probe displayed a specific Zn2+ induced blue shift at the spectral maximum values of excitation (80 nm) and emission (30 nm). The ratio imaging capability of Zn2+ under dual excitation mode can be applied not only to quantitative and reversible detection of exogenous Zn2+, but also the observation of the Zn2+ level change under ER stress, elucidating the different behaviors of Zn2+ release in ER stimulated by tunicamycin and thapsigargin. Additionally, the NIR imaging capability of ER-Zn provides an important basis for further research on animal models and is expected to realize the visualization and treatment of ER stress-related diseases through the regulation of ER stress by Zn2+. We envision that this probe can be applied to screen drugs for diseases related to ER stress regulation.